HUBUNGAN EFIKASI DIRI DENGAN MEKANISME KOPING PADA REMAJA KORBAN PERCERAIAN DI SEKOLAH MENENGAH PERTAMA WILAYAH KABUPATEN JEMBER - Erti Ikhtiarini Dewi; Novia Narulia Sari; Enggal Hadi Kurniyawan (Universitas Bengkulu, 2025)
Introduction: Parental divorce has significant negative impacts on children’s psychological well-being, particularly in adolescents. Self-efficacy, which is influenced by an individual’s belief in their own abilities, is believed to influence the coping mechanisms employed when dealing with stressors. This study aims to analyze the relationship between self-efficacy and coping mechanisms among adolescents affected by parental divorce in junior high schools in Jember Regency. Method: this study used a correlational design with a cross-sectional approach. The respondents were 60 adolescents aged 12-15 years selected using purposive sampling based on inclusion criteria. Data were collected using the general self-efficacy scale (GSES) to measure self-efficacy and the brief cope inventory to measure coping mechanisms. Data analysis was conducted using the kendall tau test. Result: the results showed that most respondents had high self-efficacy (91.7%) and employed adaptive coping mechanisms (90%). there was a significant positive relationship between self-efficacy and coping mechanisms (p-value = 0.000; r = 0.362). Analysis: these findings suggest that adolescents with high self-efficacy tend to be more able to use adaptive coping strategies. It is important to get support in building self-efficacy and understanding of adaptive coping mechanisms so that they can adjust well. Discussion: nurses as educators can teach effective coping strategies and can provide emotional support through counseling sessions. The role model method can be used to use emotional management that can be applied by adolescent victims of divorce. Keywords : adolescents, coping mechanisms, parental divorce, self-efficacy